2023
DOI: 10.24326/asphc.2023.4329
|View full text |Cite
|
Sign up to set email alerts
|

The impact of foliar dikegulac and Asahi SL sprays on the shoot production of highbush blueberry nursery plants

Abstract: The aim of the present study was to assess the usefulness of dikegulac (2,3:4,6-di-O-isopropylidene-α-Lxylo-2-hexulofuranosonic acid) and Asahi SL (sodium ortho- and para-nitrophenolate, sodium 5-nitroguaiacolate) in production of highbush blueberry nursery plants. The experiment was carried out on three cultivars of highbush blueberry: ‘Bluecrop’, ‘Brigitta blue’ and ‘Darrow’. Pot plants were treated two times with dikegulac (0.1%) or/and Asahi SL (0.2%) foliar sprays in the late spring. The reaction of blueb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It has been shown in several studies that melatonin has auxin-like activities [ 47 49 ]. In highbush blue berry melatonin could replace indole butyric acid (IBA) in vitro and enhanced shoot morphogenesis [ 50 ]. The higher shoot regeneration and transformation rate obtained in our study in melatonin treated calli could also be due to its auxin–like activity which may enhance organogenesis and shoot regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in several studies that melatonin has auxin-like activities [ 47 49 ]. In highbush blue berry melatonin could replace indole butyric acid (IBA) in vitro and enhanced shoot morphogenesis [ 50 ]. The higher shoot regeneration and transformation rate obtained in our study in melatonin treated calli could also be due to its auxin–like activity which may enhance organogenesis and shoot regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that melatonin can boost shoot growth and regulate shoot development by influencing numerous physiological processes [67]. Exogenous application of melatonin, for example, has been shown to improve shoot growth and amplify the expression of genes involved in shoot development in vitro in blueberry [68]. Increased production of shoots has been observed for exogenous melatonin application in mimosa, pomegranate, and blueberry [68][69][70].…”
Section: Function Of Melatonin In Shoot Growth and Differentiation In...mentioning
confidence: 99%
“…Exogenous application of melatonin, for example, has been shown to improve shoot growth and amplify the expression of genes involved in shoot development in vitro in blueberry [68]. Increased production of shoots has been observed for exogenous melatonin application in mimosa, pomegranate, and blueberry [68][69][70]. Melatonin has also been associated with differential patterning of branching and leaf production [24,71].…”
Section: Function Of Melatonin In Shoot Growth and Differentiation In...mentioning
confidence: 99%